A Review of Amoebic Liver Abscess for Clinicians in a Nonendemic Setting. (2012) - Wuerz, Terry; Kane, Jennifer B; Boggild, Andrea K; Krajden, Sigmund; Keystone, Jay S; Fuksa, Milan; Kain, Kevin C; Warren, Ralph; Kempston, John; Anderson, Joe
Abstract : Amoebic liver abscess (ALA) is an uncommon but potentially life-threatening complication of infection with the protozoan parasite Entamoeba histolytica. E histolytica is widely distributed throughout the tropics and subtropics, causing up to 40 million infections annually. The parasite is transmitted via the fecal-oral route, and once it establishes itself in the colon, it has the propensity to invade the mucosa, leading to ulceration and colitis, and to disseminate to distant extraintestinal sites, the most common of which is the liver. The authors provide a topical review of ALA and summarize clinical data from a series of 29 patients with ALA presenting to seven hospitals in Toronto, Ontario, a nonendemic setting, over 30 years.